2017
DOI: 10.1159/000481975
|View full text |Cite
|
Sign up to set email alerts
|

Response Gene to Complement-32 Promotes the Imbalance of Treg/Th17 in Patients with Dilated Cardiomyopathy

Abstract: Background/Aims: The imbalance of Treg/Th17 cells plays important role in the pathogenesis of dilated cardiomyopathy (DCM). Response gene to complement (RGC)-32 is a cell cycle regulator that plays an important role in cell proliferation. We evaluated whether the upregulation of RGC-32 was implicated in the homeostasis of Treg/Th17 cells in DCM. Methods:The levels of plasma RGC-32, IL-17 and TGF-β1, and the frequencies of circulating CD4 + RGC-32 + T cells, Th17 and Treg cells in patients with DCM were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Pathological activation of circulating CD4 + T-cells and production of IgG autoantibodies against certain antigens have been identified in DCM patients [9,10,42]. In parallel, an alteration of Treg and Th17 proportions in peripheral blood was identified in these patients [14]. The results obtained in this study, in both patients and a mouse model, agree with the previously described observations, and indicate that CD4 + T-cell activity and functions are altered during DCM development.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Pathological activation of circulating CD4 + T-cells and production of IgG autoantibodies against certain antigens have been identified in DCM patients [9,10,42]. In parallel, an alteration of Treg and Th17 proportions in peripheral blood was identified in these patients [14]. The results obtained in this study, in both patients and a mouse model, agree with the previously described observations, and indicate that CD4 + T-cell activity and functions are altered during DCM development.…”
Section: Discussionsupporting
confidence: 90%
“…Despite therapeutic progress, further research has shown that some patients remain vulnerable to sudden cardiac death and refractory heart failure, requiring heart transplantation or mechanical circulatory support [2]. A handful of previous studies have reported that immune dysfunction induced by autoimmune disorders plays a vital role in the progression of DCM [3][4][5][6][7][8][9][10][11][12][13][14]. T-cell-mediated immune dysfunction has been linked to a variety of heart diseases, including idiopathic DCM [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β1 as a multifunctional cytokine is involved in pathological processes, such as inflammatory response and tumorigenesis [37][38][39] . RGC-32 is a downstream target of TGF-β that mediates epithelialmesenchymal transition and Th17 cell differentiation 40,41 . In this study, our data indicated that RGC-32 expression in macrophages was significantly increased by colon cancer cell-derived TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Extensive researches have shown that RGC-32 induces cell proliferation, differentiation, invasion, migration, epithelial-mesenchymal transition (EMT) occurrence and metabolism. [12][13][14][15][16] A considerable amount of literatures have been published on regulatory effects of RGC-32 in a variety of non-cancerous diseases, concerning vascular diseases, [17][18][19] Alzheimer's Disease, 20 obesity, 21 diabetic retinopathy, 22 autoimmune encephalomyelitis, 23 renal ischemia reperfusion injury, 24 preeclampsia 25 and other non-tumour diseases. In addition to its mediating role in non-cancer, essential roles of it were identified to facilitate the progressions of numerous malignancies, namely ovarian cancer, 26,27 colon cancer, 28,29 prostate cancer, 30 lung cancer, 31,32 breast carcinoma 33 and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%